2018
DOI: 10.12688/f1000research.12490.3
|View full text |Cite
|
Sign up to set email alerts
|

Maize Phyllosphere Microbial Community Niche Development Across Stages of Host Leaf Growth

Abstract: Background: The phyllosphere hosts a variety of microorganisms, including bacteria, which can play a positive role in the success of the host plant. Bacterial communities in the phylloplane are influenced by both biotic and abiotic factors, including host plant surface topography and chemistry, which change in concert with microbial communities as the plant leaves develop and age. Methods: We examined how the Zea mays L. leaf microbial community structure changed with plant age. Ribosomal spacer length and sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
2
1
0
Order By: Relevance
“…The moderate but significant effect of management regime on soil prokaryotic communities was consistent with results of a previous study that compared organic and conventional management systems . As with fungal communities, changes in aboveground and root prokaryotic communities based on plant growth stage and sampling timepoint are consistent with the results of previous studies on maize and rice (Manching et al, 2017;Edwards et al, 2018). Differences in assembly between above and belowground tissues may alter the community's ability to respond to agricultural management and plant growth.…”
Section: Discussionsupporting
confidence: 86%
“…The moderate but significant effect of management regime on soil prokaryotic communities was consistent with results of a previous study that compared organic and conventional management systems . As with fungal communities, changes in aboveground and root prokaryotic communities based on plant growth stage and sampling timepoint are consistent with the results of previous studies on maize and rice (Manching et al, 2017;Edwards et al, 2018). Differences in assembly between above and belowground tissues may alter the community's ability to respond to agricultural management and plant growth.…”
Section: Discussionsupporting
confidence: 86%
“…In particular, we have shown a role for temporal variation, alone and in interaction with habitat and host species, as an important driver of bacterial community composition variation, especially in the phyllosphere. While succession of microbial communities in the phyllosphere has been documented previously ( Redford and Fierer, 2009 ; Wagner et al, 2016 ; Manching et al, 2017 ), here we have shown that even in a rotation of annual crops, the patterns of bacterial succession within and among years are an important driver of community structure.…”
Section: Discussionsupporting
confidence: 65%
“…After their arrival on the leaf, microorganisms face host and environmental factors that can act as an assembly filter by either supporting or preventing establishment (Figure 1). Such filtering is consistent with communities that track leaf traits over time, as well as with repeated associations of microorganisms across host replicates and seasons (40,89). Host filtering may be passive, with microbial taxa succeeding or failing based on the suitability of leaf conditions or ability to handle the host immune system.…”
Section: Introduction 1foliar Microbiomes As Extended Plant Phenotype...mentioning
confidence: 53%